Health system's readiness to provide cardiovascular, diabetes and chronic respiratory disease related services in Nepal: analysis using 2015 health facility survey - Umesh Ghimire; Nipun Shrestha; Bipin Adhikari; Suresh Mehata; Yashashwi Pokharel; Shiva Raj Mishra (BMC, 2020)
Abstract Background The burgeoning rise of non-communicable diseases (NCDs) is posing serious challenges in resource constrained health facilities of Nepal. The main objective of this study was to assess the readiness of health facilities for cardiovascular diseases (CVDs), diabetes and chronic respiratory diseases (CRDs) services in Nepal. Methods This study utilized data from the Nepal Health Facility Survey 2015. General readiness of 940 health facilities along with disease specific readiness for CVDs, diabetes, and CRDs were assessed using the Service Availability and Readiness Assessment manual of the World Health Organization. Health facilities were categorized into public and private facilities. Results Out of a total of 940 health facilities assessed, private facilities showed higher availability of items of general service readiness except for standard precautions for infection prevention, compared to public facilities. The multivariable adjusted regression coefficients for CVDs (β = 2.87, 95%CI: 2.42-3.39), diabetes (β =3.02, 95%CI: 2.03-4.49), and CRDs (β = 15.95, 95%CI: 4.61-55.13) at private facilities were higher than the public facilities. Health facilities located in the hills had a higher readiness index for CVDs (β = 1.99, 95%CI: 1.02-1.39). Service readiness for CVDs (β = 1.13, 95%CI: 1.04-1.23) and diabetes (β = 1.78, 95%CI: 1.23-2.59) were higher in the urban municipalities than in rural municipalities. Finally, disease-related services readiness index was sub-optimal with some degree of variation at the province level in Nepal. Compared to province 1, province 2 (β = 0.83, 95%CI: 0.73-0.95) had lower, and province 4 (β =1.24, 95%CI: 1.07-1.43) and province 5 (β =1.17, 95%CI: 1.02-1.34) had higher readiness index for CVDs. Conclusion This study found sub-optimal readiness of services related to three NCDs at the public facilities in Nepal. Compared to public facilities, private facilities showed higher readiness scores for CVDs, diabetes, and CRDs. There is an urgent need for policy reform to improve the health services for NCDs, particularly in public facilities.